Comparison of the Effectiveness of the Satir Communication Model and Compassion-Based Cognitive Behavioral Therapy on Behavioral Flexibility and Anxiety Sensitivity in Couples with Marital Conflict - Jamali, Marjan; Heidari, Hasan; Davoodi , Hossein; Ghaffari , Khalil (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to compare the effectiveness of compassion-based cognitive behavioral therapy with the Satir communication model on behavioral flexibility and anxiety sensitivity in couples experiencing marital conflict. Methods and Materials: The statistical population consisted of couples with marital conflicts who visited counseling centers in Tehran in 2023. The research method was a quasi-experimental design with a non-equivalent control group, pre-test, post-test, and follow-up. Participants were randomly assigned into two groups of 15, matched for comparability. The research instruments were the Anxiety Sensitivity Index by Floyd et al. (2005) and the Connor-Davidson Resilience Scale by Connor and Davidson (2003). The first experimental group received the Satir communication model, and the second group underwent compassion-based cognitive behavioral therapy over eight sessions. Data were analyzed using SPSS through a two-way repeated measures analysis of variance. Findings: The results showed that both compassion-based cognitive behavioral therapy and the Satir communication model led to an increase in behavioral flexibility and a decrease in anxiety sensitivity in couples with marital conflicts (P<0.001); furthermore, compassion-based cognitive behavioral therapy was found to be more effective between the two approaches. Conclusion: The findings confirm the impact of both the Satir communication model and compassion-based cognitive behavioral therapy on improving behavioral flexibility and reducing anxiety sensitivity in couples.